(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Social media has become a key term in Media and Communication Studies and public discourse for characterizing platforms such as Facebook, Twitter, YouTube, Wikipedia, LinkedIn, Wordpress, Blogspot, Weibo, Pinterest, Foursquare and Tumblr. This paper discusses the role of the concept of the public sphere for understanding social media critically. It argues against an idealistic interpretation of Habermas and for a cultural-materialist understanding of the public sphere concept that is grounded in political economy.The media in a number of Western countries, including Australia, could be forgiven for envying the growth of the Indian media in recent decades. In contrast to more mature media markets in Australia and elsewhere, the Indian media is surviving the onslaught of new media technologies including social media platforms available to news audiences as an alternative to traditional news media. However, despite the omnipresence and diversity of over 800 television channels, over 94,000 publications and hundreds of radio stations, the ‘commercial’ imperative of Indian news media has raised doubts about their capacity to meet the ‘ideals’ of the public sphere. This paper examines the Indian public sphere in terms of citizens’ increasing use of various social media platforms to express their anger, frustration and protest against the system of governance and corruption.It explores the increased utilisation of social media platforms by youth and the middle class, who have often remained disengaged with governance in the country, as a sign of deepening democracy and widening public sphere in India, despite the ‘digital divide’ that still exists in the country.